Forensic Assistance Project: Consultant Report 1999-037 Glamoč I Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Komar, Debra On July 20 and 22, 1999 the Republika Srpska Commission on Tracing Prisoners and Missing Persons investigated four sites in the Glamoč area and recovered three individuals. The remains were all recovered from shallow marked graves. Two were secondary burials of surface remains. Place of Exhumation: Glamoč Exhumation Site: Vodenica, Zajaruga, Glamoč, Rore Date of Exhumation: 20-22 July 1999 Minimum Number of Exhumed Individuals: 003